The effectiveness of internal control systems used by parastatals in Zimbabwe in reducing the risk of fraud - Takavingofa, Tsitsi G. (Midlands State University, 2017)
This research is an investigation into the effectiveness of internal control systems being employed by Zimbabwe Parastatals in reducing the risk of fraud. The objectives of the research are to evaluate the effectiveness of the internal controls currently being used by Parastatals in reducing fraud and to give recommendations on what can be done to improve their effectiveness .Literature reviewed showed that ineffective internal controls provide an opportunity for fraudulent activities to happen in Parastatals. The researcher used stratified sampling technique whereby the target population was divided into stratus which includes mining, agriculture transport, telecommunication, health etc. The major finding of this research is that internal controls currently being employed are ineffective. The researcher recommended that Parastatals should formulate and implement corporate fraud policies as well as bringing about the concept of enterprise wide risk management in their system.